QUADRANT ANALYSIS OF TOTAL FERTILITY RATE AND CONTRACEPTIVE PREVALENCE RATE OF DISTRICT AND CITY IN EAST JAVA - Kiki Adi Mutiari; Kuntoro Kuntoro (Universitas Airlangga, 2020)
One of the indicators determine the wellness of Family Planning Program is the high number of participants enrolling, or commonly known as the Contraceptive Prevalence Rate (CPR) and the number of children born known as the Total Fertility Rate (TFR) of a maximum of 2 children. There are several regions in East Java where the situation of TFR and CPR does not show the ideal conditions. This shows that there are problems in the current family planning program. This research was conducted to map districts and cities in East Java based on TFR and CPR data respectively in quadrant form. This type of research is on-reactive research which utilizes secondary data from Indonesia - National Socio-Economic Survey in 2015. The research method used is recapitulating data and classifying districts and cities in the form of quadrants by comparing to data on achievement of TFR and CPR in East Java using SPSS. The results of the study have mapped districts and cities in East Java which are described in quadrant form. The regions that need major attention from the government are regions in quadrants I and II. Quadrant III is included in an abnormal condition and quadrant IV is a quadrant that has an area where TFR and CPR conditions are ideal. The conclusions of this study are the areas in quadrant I, namely: Sampang (district), Blitar (city), Blitar (district), Tulungagung (district), Ponorogo (district), Madiun (city), and Pasuruan (city) are the priority in getting the FP program improvements. The advice that can be given is to evaluate the ongoing family planning program to find out the factors that cause the TFR and CPR conditions are not in line with government expectations.